Pemberdayaan Kelompok Wanita Tani dengan Diversifikasi Produk Olahan Popcorn Jagung Manis - Chandra, M Andi; Marliadi, Reny; Setia, Lisa; Wahyudi, Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
KWT Gangga has never processed sweet corn into a product because it does not yet have the skills to process sweet corn which is ready to sell on the market in the form of popcorn. The aim of this community service is to empower the community, especially housewives or groups of women farmers, to increase the added value of commodities using corn as the raw material to become a product that has marketable value and can increase household income. The method used is counseling and training in making sweet corn popcorn. The counseling includes several activities such as the introduction of sweet corn, processed sweet corn products and training on how to make sweet corn popcorn. During the training in this service activity, the participants were directly and actively involved in all series of activities. The results achieved in this activity were an increase in KWT Gangga's knowledge in utilizing agricultural products in the form of sweet corn which can add to processed products, by making sweet corn popcorn. Increased knowledge with a value percentage of 70%. The follow-up plan for the service activities that have been carried out is that there is also a need for assistance with product PIRT applications in order to expand sales of processed KWT products.